A review on composite materials and process parameters optimisation for the fused deposition modelling process. Issue 1 (2nd January 2017) - Mohan, N.; Senthil, P.; Vinodh, S.; Jayanth, N.
ABSTRACT: Fused deposition modelling is the most significant technique in additive manufacturing (AM) that refers to the process where successive layers of material are deposited in a computer-controlled environment to create a three-dimensional object. The main limitations of using fused deposition modelling (FDM) process in the industrial applications are the narrow range of available materials and parts fabricated by FDM are used only as demonstration or conceptual parts rather than as functional parts. Recently, researchers have studied many ways in order to increase the range of materials available for the FDM process which resulted in the increase in the scope of FDM in various manufacturing sectors. Most of the research are focussed on the composite materials such as metal matrix composites, ceramic composites, natural fibre-reinforced composites and polymer matrix composites. This article intends to review the research carried out so far in developing samples using different composite materials and optimising their process parameters for FDM in order to improve different mechanical properties and other desired properties of the FDM components.